Design of compact circular resonator for electrodeless microwave plasma lamp. Issue 16 (1st August 2013) - Yuan, Jiade; Lin, Guoqing; Chen, Heping; Su, Kaixiong
Abstract : A compact circular resonator for a microwave plasma lamp is designed. A disc‐shaped metal sheet is loaded in the coaxial resonant cavity to reduce the volume by increasing its equivalent capacitance. The operating centre frequency of the proposed circular resonator is 444.5 MHz with a radius of 25 mm and height of 40 mm. The proposed compact resonator does not need to be filled with dielectric material, therefore it is very easy to manufacture with low cost. The test results show that the proposed resonator exhibits good performance.